PFKFB3 facilitates cell proliferation and migration in anaplastic thyroid carcinoma via the WNT/β‐catenin signaling pathway - Deng, Jinmei; Cheng, Yanglei; Li, Hai; He, Xiaoying; Yu, Shuang; Ma, Jiajing; Li, Xuhui; Chen, Jie; Xiao, Haipeng; Guan, Hongyu; Li, Yanbing (Endocrine, 2024)
Purpose Despite the involvement of 6‐phosphofructo‐2‐kinase/fructose‐2,6‐biphosphatase3 (PFKFB3) in the proliferation and metastasis of diverse tumor types, its biological functions and related molecular mechanisms in anaplastic thyroid carcinoma (ATC) remain largely unclear. Methods Datasets from the Gene Expression Omnibus, the Cancer Genome Atlas and immunohistochemistry (IHC) analyses were employed to measure the expression level of PFKFB3 in ATC. A series of assays were performed to analyze the role of PFKFB3 and its inhibitor KAN0438757 in ATC cell proliferation and migration. Furthermore, Western blotting (WB), IHC and luciferase reporter assay were conducted to investigate the potential mechanisms underlying the involvement of PFKFB3 and KAN0438757 in ATC. Additionally, we established a subcutaneous xenograft tumor model in nude mice to evaluate the in vivo tumor growth. Results PFKFB3 exhibited a significant increase in its expression level in ATC tissues. The overexpression of PFKFB3 resulted in the stimulation of ATC cell proliferation and migration. Furthermore, this overexpression was associated with the elevated expression levels of p-AKT (ser473), p-GSK3α/β (ser21/9), nuclear β-catenin, fibronectin1 (FN1), matrix metallopeptidase 9 (MMP-9) and cyclin D1. It also promoted the nuclear translocation of β-catenin and the transcription of downstream molecules. Conversely, contrasting results were observed with the downregulation or KAN0438757-mediated inhibition of PFKFB3 in ATC cells. The selective AKT inhibitor MK2206 was noted to reverse the increased expression of p-AKT (ser473) and p-GSK3α/β (ser21/9) induced by PFKFB3 overexpression. The level of lactate was increased in PFKFB3-overexpressing ATC cells, while the presence of KAN0438757 inhibited lactate production. Moreover, the simultaneous use of PFKFB3 downregulation and KAN0438757 was found to suppress subcutaneous tumor growth in vivo. Conclusion PFKFB3 can enhance ATC cell proliferation and migration via the WNT/β-catenin signaling pathway and plays a crucial role in the regulation of aerobic glycolysis in ATC cells.